An Overview of Basic Theoretical Physics - A W Joshi; K D Abhyankar (Hyderabad, 2009)
This book covers both the pre-quantum and post-quantum development of theoretical physics in a straightforward but fairly rigorous style. Unlike most modern physics courses which gloss over the basic physic subjects in preference to specialised topics like solid state physics, electronics, plasma physics, nanotechnology, cosmology, astrophysics and computer science, this book brings together the various branches of theoretical physics on one platform to give a panoramic view of the subject. The first four chapters of the book deal with the classical topics of Hamiltonian mechanics, theories of relativity, electromagnetic theory of radiation and thermodynamics. They are followed by chapters on atomic spectra and quantum mechanics, spectra of diatomic molecules, quantum theory of radiation, statistical mechanics, and nuclear and particle physics. Guided exercises form a unique feature of this book. The broad coverage of topics in theoretical physics makes this book an invaluable reference for senior undergraduate and postgraduate students of all branches of physics as well as research workers and physics teachers. The book will also serve for a foundation course for allied subjects such as astrophysics, geophysics, meteorology, laser physics and plasma physics.
English
Keywords: Chemistry; Physics